Impact of COVID-19 on functional, cognitive, neuropsychiatric, and health-related outcomes in patients with dementia: A systematic review - Lucia Crivelli; Andrea Winkler; Greta Keller; Simone Beretta; Ismael Luis Calandri; Wouter De Groote; Arianna Fornari; Jennifer Frontera; Miia Kivipelto; Ana Sabsil Lopez-Rocha; Francesca Mangialasche; Daniel Munblit; et al. (eNeurologicalSci)
Background: This systematic review analyzes the impact of COVID-19 on dementia patients' functional, cognitive, neuropsychiatric, and health related outcomes. It hypothesizes that dementia patients infected with SARS-CoV-2experience more pronounced deterioration compared to those who are uninfected. Methods: Research from 01/03/2020 to 07/10/2023 was conducted using Medline, Web of Science, and Embase databases, and adhering to PRISMA guidelines and the PICO framework. The study aimed to determine if SARS-CoV-2 infection is associated with worse outcomes in dementia patients. The protocol is registered in PROSPERO (CRD42022352481), and bias was evaluated using the Newcastle-Ottawa Scale. Results: Among 198 studies reviewed, only three met the criteria. Chen et al. (2023) identified higher mortality in SARS-CoV-2-infected dementia patients, while Merla et al. (2023) observed faster cognitive decline in infected individuals with increased hospital admissions. Additionally, Cascini et al. (2022) reported an increased risk of infection and significantly elevated mortality in dementia patients, highlighting comorbidities and antipsychotic medication use as key risk factors. Conclusion: These limited data suggest higher mortality and cognitive decline in dementia patients following COVID-19, underscoring the need for extensive research in this area.